Chemical Composition, Antibacterial and Antibiotic-Modifying Activity of Croton grewioides Baill Essential Oil - José Jonas Ferreira Viturino; Cicera Janaine Camilo; Natália Kelly Gomes de Carvalho; Joice Barbosa do Nascimento; Maria Inacio da Silva; Mariana Pereira da Silva; José Walber Gonçalves Castro; Geane Gabriele de Oliveira Souza; Fabíola Fernandes Galvão Rodrigues; José Galberto Martins da Costa (Future Pharmacology)
Background: Croton grewioides Baill., a species native to the Caatinga, popularly known as canela de cunhã, is used in traditional medicine to treat gastrointestinal diseases such as diarrhea, gastritis and stomach ulcers. The combination of essential oils with antibiotics reveals several beneficial effects associated with the increased efficacy of these drugs against pathogenic agents. Through this perspective, this study aimed to identify the chemical composition of the essential oil of C. grewioides (OECG) and evaluate its antibacterial and antibiotic-modifying activities against standard and multiresistant bacteria. Methods: To analyze the compounds present in the oil, the techniques of gas chromatography coupled with mass spectrometry (GC/MS) and gas chromatography with a flame ionization detector (GC/FID) were used. In the bacteriological tests, the Minimum Inhibitory Concentration (MIC) was obtained by the broth microdilution technique. The modulating effect of the essential oil was determined by calculating the subinhibitory concentration, followed by a serial microdilution of the antibiotics. The MIC reduction factor (CRF) was calculated, and its data were expressed as a percentage. Results: The analysis of the chemical composition identified the presence of the major compound estragole with a relative abundance of 50.34%. The MIC values obtained demonstrated efficacy in K. pneumoniae isolated from urine with MIC values of 512 µg/mL. OECG potentiated the effects of all antibiotics tested on the strains S. aureus ATCC 29213, K. pneumoniae Carbapnemase, E. coli ATCC 25922 and S. aureus ATCC 29213 with their CRF of 97.65%, 99.80%, 99.85% and 99.88%, respectively. Conclusions: Thus, the essential oil of C. grewioides presents synergistic effects when combined with the antibiotics tested, in addition to acting in the fight against bacterial resistance to antibiotics.